The genome sequence of the Hungarian meadow viper, Vipera ursinii rakosiensis Méhely, 1893 [version 1; peer review: 2 approved] - Bálint Halpern; Ann M. Mc Cartney; Alice Mouton; Judit Vörös; Giulio Formenti (Wellcome Open Research)
We present a genome assembly from an individual female Vipera ursinii rakosiensis (the Hungarian meadow viper; Chordata; Lepidosauria; Squamata; Viperidae). The genome sequence is 1,625.0 megabases in span. Most of the assembly is scaffolded into 19 chromosomal pseudomolecules, including the W and Z sex chromosomes. The mitochondrial genome has also been assembled and is 17.38 kilobases in length.